A Study of Factors Associated with Presence of ARIIN Children 1-4 Years of Age in An Urban Slum of Pune City - Jha, Ajay Kumar; Bhawalkar, Jitendra S; Dixit, Anil K; Pawaiya, Amit Singh; Pathak, Nitin K (National Journal of Community Medicine, 2014)
Objective: To study the incidence Acute respiratory infection (ARI) in children 1-4years in an urban slum. Background: Every year some 12 million children in developing countries die before they reach their fifth birthday, many during the first year of life. 7 in 10 deaths are due to acute respiratory infections, diarrhea, measles, malaria or malnutrition or a combination of these conditions. Materials and Method: A longitudinal survey of all children who were in the age group 1-4 years residing in the Landewadi slum, Pune. It was carried out from Nov 2008- Dec 2009. Data on symptoms suggesting ARI, cough, fever and nasal discharge, were collected for the preceding 7 days by recall. Results: There were 346 households from which 195 children formed the study population. Association between age in months and history ofARI among the study population shows that there were 25.4% of children between 13-24 months age-group followed by 25-36 months age group 18.7 % and the lowest was in the 37-48 months age group 7.5 % suffering from acute respiratory infection. Conclusions: In study found that there was no significant association between ARI with age, sex and some risk factors for ARI.Where as indoor air pollution was the significant risk factor responsible for ARI in children.